Relationship between the nutritional status of banana plants and black sigatoka severity in the Magdalena region of Colombia (2015)
The association between the severity (average percentage of infection-API) by Mycosphaerella fijiensis M. Morelet and the plant nutrient content in the Banana Growing Zone of the Department of Magdalena (Colombia) was established. Between 2011 and 2012, the foliar contents of N, P, K, Ca, Mg, Na, S, Cu, Fe, B, Zn, and Mn were determined in sectors with high, medium, and low incidences in order to establish their relationships with the API. Severity was determined with the Stover and Dickson methodology, modified by Gauhl for bananas, in order to obtain sanitary information for the zone. With the obtained data, a correlation analysis was completed and the ordination technique was utilized to establish the relationships between farms and variables using an Euclidean distance. The differences between the farms and years were estimated with a two way analysis of variance with permutations and a canonical discrimination analysis in order to differentiate the farms using the measured foliar variables. The results highlighted the importance of the appropriate and balanced management of site-specific nutritional plans for the management of black sigatoka.